Interaction of obesity with smoking and inflammatory arthropathies increases the risk of periprosthetic joint infection: a propensity score matched study in a Chinese Han population. Issue 2 (February 2019) - Xu, C.; Guo, H.; Wang, Q.; Qu, P.; Bell, K.; Chen, J.
Summary: Background: Although a large number of studies have identified obesity as an independent risk factor for the development of periprosthetic joint infection (PJI), the synergistic impacts of obesity with other factors on PJI remain unknown. Additionally, few studies have specifically explored the risk factors of PJI within a Chinese population. Aims: To investigate the association between obesity and PJI in a Chinese population, and identify synergistic impacts of obesity with other risk factors on the development of PJI. Methods: Three hundred and seven patients at a single institution with a diagnosis of PJI following primary total hip or knee arthroplasty, treated from 2008 to 2015, were identified. Each case was matched with two controls who did not develop PJI after primary total hip or knee arthroplasty in the study period using propensity score matching for several important parameters. Multi-variable logistic regression models were used to estimate the association between body mass index (BMI) and the risk of developing PJI. Interaction and stratified analyses were conducted according to age, sex, type of surgery, smoking status, alcohol use, diabetes, inflammatory arthritis, liver disease and renal disease. Findings: The multiple logistic analyses showed that obesity was associated with increased risk of PJI [odds ratio (OR) 2.48; 95% confidence interval (CI) 1.66–3.69]. When analysed as a continuous variable, BMI was also associated with increased risk of PJI (OR per 1 kg/m 2 increase in BMI 1.08; 95% CI 1.02–1.14). In the interaction analysis, patients who were obese and smoked had a higher OR of developing PJI than non-smokers who were obese (OR 3.54 vs 1.55, P -value for interaction=0.031). Similarly, the OR was much higher for patients with both obesity and inflammatory arthritis than for patients who were obese with no history of inflammatory arthritis (OR 3.9 vs 1.55, P -value for interaction=0.029). No other significant interactions were found in the association between obesity and PJI. Conclusion: Obesity is an independent risk factor for the development of PJI in the Chinese Han population. Surgeons should be aware that obese patients who smoke or have inflammatory arthritis are at additional increased risk of PJI.